Methods of increasing physical faiths during the training of football players - R. Hamroqulov; Sh. Nishonov (Zien Journals, 2022)
The article explains the further development of the physical capabilities of football players by increasing the volume and intensity of loads in the annual training cycle during training.
Keywords: Increase in physical capacity; the annual training cycle; the period of preparation